(untitled) (gjstudies, 2021)
The contemporary corporate landscape faces unprecedented scrutiny regarding environmental stewardship, social responsibility, and governance transparency. Traditional financialauditing, while essential for verifying financial statements, increasingly proves insufficientfor addressing the multifaceted accountability demands of modern stakeholders. Environmental, Social, and Governance (ESG) audits emerge as a critical innovation in corporateoversight, bridging the gap between financial performance and broader societal impact. Thisresearch explores the transformative potential of ESG audits through a novel computationalframework that integrates artificial intelligence with established auditing principles.Corporate accountability has evolved beyond mere financial compliance to encompassenvironmental impact, social equity, and ethical governance. The limitations of conventional auditing methodologies become apparent when confronting complex sustainabilitychallenges, supply chain transparency issues, and stakeholder engagement metrics. ESGaudits represent a paradigm shift in how organizations measure and report their comprehensive performance, yet the methodological rigor and computational sophistication requiredfor effective ESG auditing remain underdeveloped.